2015
DOI: 10.1155/2015/191856
|View full text |Cite
|
Sign up to set email alerts
|

Successful Strategies to Engage Research Partners for Translating Evidence into Action in Community Health: A Critical Review

Abstract: Objectives. To undertake a critical review describing key strategies supporting development of participatory research (PR) teams to engage partners for creation and translation of action-oriented knowledge. Methods. Sources are four leading PR practitioners identified via bibliometric analysis. Authors' publications were identified in January 1995–October 2009 in PubMed, Embase, ISI Web of Science and CAB databases, and books. Works were limited to those with a process description describing a research project… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 65 publications
1
50
0
4
Order By: Relevance
“…interviews, participation in advisory councils) and researcher and co-design participant communication and relationships have also been recommended (e.g. [5,14,15]). However, the current literature is complex, contradictory and poorly synthesised as it has been examined from several different research perspectives in studies focused on maximising rigor and completeness for academic understanding rather than on providing practitioners with a short, parsimonious and accessible synthesis of the most significant characteristics of the literature.…”
Section: Introductionmentioning
confidence: 99%
“…interviews, participation in advisory councils) and researcher and co-design participant communication and relationships have also been recommended (e.g. [5,14,15]). However, the current literature is complex, contradictory and poorly synthesised as it has been examined from several different research perspectives in studies focused on maximising rigor and completeness for academic understanding rather than on providing practitioners with a short, parsimonious and accessible synthesis of the most significant characteristics of the literature.…”
Section: Introductionmentioning
confidence: 99%
“…26 Salsberg et al identified the most commonly referenced strategies for effective partnerships as: ( a ) development of an advisory structure; ( b ) development of research agreements, ( c ) use of group facilitation techniques, ( d ) hiring staff from the community of study; and ( e ) frequent communication. 27 Many authors identify trust and respect, along with opportunities for face-to-face interaction and clear roles and expectations as essential. 9,31-35 Others stress the need for brokering, boundary-spanning or coordinating roles, as well as skills in change management.…”
Section: Introductionmentioning
confidence: 99%
“…Reasons for unsuccessful or non-implementation of guidelines in clinical practice are now being recognized beyond the lack of knowledge, including (lack of) comprehensiveness, relevance, simplicity, applicability and presence of (negative) role models [14]. Our strategy of self-assessment of the ICU team after the failed attempt to implement PLR testing (period 2) may be referred as a form of ‘participatory action research,’ initially implemented in community health medicine [17]. Such form of participation may also be transformed to involvement of ICU personnel in the analysis of reasons for ‘knowledge-to-care gaps’ and potential solutions [18].…”
Section: Discussionmentioning
confidence: 99%